Tall story - GOURLAY, CANDY; Candy Gourlay
Andi, a basketball-obsessed girl in London, and her long-lost half-brother, Bernardo, an 8-foot-tall teenager with gigantism from the Philippines.
Keywords: contemporary young adult novel that blends Philippine folklore with a modern story of immigration and family; accepting one's uniqueness, overcoming cultural transitions, and finding strength in family connections